Design And Development of An Internet of Things-based Smartbell Using ESP32-Cam And Telegram - Rakhmawati, Puji Utami; Syahnaryanti, Dinda Mareta; Rizdania; Sumantri (Primakara University, 2026)
When guests or couriers arrive, homeowners must go to the front door to identify them due to the limitations of conventional doorbells, which only produce sound. If the homeowner is not at home, they may miss the arrival of guests, and couriers might leave packages elsewhere, posing a risk of loss since there is no real-time notification system. To address this issue, a Smartbell based on the Internet of Things (IoT) was designed using the ESP32-CAM module as an image capture device, integrated with Telegram to provide homeowners with real-time visual information. This study applied the prototype method, which consists of stages such as requirements identification, system design, coding, functionality and time testing, as well as system evaluation before implementation. The test results show that the Smartbell successfully performed as expected. In the simulation, when the bell button was pressed, the buzzer sounded, and the ESP32-CAM camera automatically captured an image and sent it to Telegram in real-time. Since the Smartbell was successfully connected to the Telegram bot, it can be operated remotely. Testing with a Wi-Fi network resulted in an average response time of 0.74 seconds, while using a cellular data network achieved 0.54 seconds. With a response time of less than one second from the integration of ESP32-CAM and Telegram, this system supports the homeowner’s needs as a remote and real-time guest monitoring solution.